Surviving on the frontline: Retail security guards and their self-protection behaviours - Koeppen, Benjamin (Criminology & criminal justice, 2025)
Despite the rapid expansion of private security guarding over the past 30 years, the reactions of guards to working in situations where violence is a constant possibility are seldom discussed. This article analyses how retail security guards respond to the threat of, and the actual experience of, violence through their adaptation of self-protection measures. We identify that a range of measures are adapted, broadly compromising of the ‘proactive’ that prepare guards for potential future confrontation and those described as ‘inactive’ where guards may use avoidance tactics or methods of withdrawal for their own safety. The article considers motivational factors that drive the adaptation of proactive and inactive measures and develops a novel explanatory framework outlining how fears around violence can generate both functional and dysfunctional forms of worry in security guards. Finally, some implications of these findings for the private security sector are outlined.